Holistic Management Of 8 Years Old Child With Nephrotic Syndrome Through A Family Medicine Approach - Simatupang, Devi Fila Delfia BR; Mayasari, Diana (CV. Jasa Sukses Abadi, 2025)
Nephrotic syndrome (NS) is a glomerular disorder of the kidney characterized by massive proteinuria, hypoalbuminemia, edema, and hypercholesterolemia. The global incidence of NS is approximately 1–3 cases per 100,000 children (<16 years), with a prevalence of 6 cases per 100,000 population (2–3 cases per year) in Indonesia. The male-to-female ratio is 2:1. Inappropriate management may result in recurrent relapses, increased risk of complications, and reduced patient well-being. This study represents an application of evidence-based family medicine in managing a patient with nephrotic syndrome, involving the identification of clinical problems, risk factors, and comprehensive management through a patient-centered and family approach. Primary data were obtained through alloanamnesis, physical and supporting examinations, and home visits to complement data on family, psychosocial, and environmental aspects. Evaluation was conducted holistically from the initial to the final stages of the study using both quantitative and qualitative assessments. Disease recurrence can be prevented through non-pharmacological interventions such as patient education on triggering factors. Internal factors identified in this case included a history of infection, age, and lack of awareness regarding relapse risk factors. External factors included insufficient family knowledge about nephrotic syndrome, its potential complications, and the influence of environmental factors in preventing recurrence. The diagnosis was established, and holistic management was carried out using a patient-centered and family approach, supported by relevant theories and recent studies. The patient and family have achieved the adoption stage in behavioral change.